Mistreatment in organizations - Perrewe, Pamela L.; Halbesleben, Jonathon R. B.; Rosen, Christopher C. (Emerald, 2015)
The objective of this series is to promote theory and research in the increasingly growing area of occupational stress, health and well being, and in the process, to bring together and showcase the work of the best researchers and theorists who contribute to this area. Volume 13 of Research in occupational stress and well being is focused on mistreatment in organizations. Mistreatment can be damaging to the individual as well as to the organization. This volume includes critical topics on customer mistreatment, aggression in the workplace, incivility, and workplace ostracism. We consider mistreatment to be a "workplace stressor" which has been linked to higher emotional burnout, withdrawal behaviors such as tardiness and absenteeism, and lower customer service performance. This is just one example of how mistreatment can affect employees negatively. The topic of this volume, Mistreatment in Organizations, is sure to attract the attention of researchers around the globe.
Keywords: Employees -- Abuse of.; Quality of work life.; Job stress.; Customer relations.; elektronické knihy; electronic books